2014
DOI: 10.1186/1472-6882-14-117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo antitrypanosomal activity of crude extracts of Artemisia abyssinica against aTrypanosoma congolense isolate

Abstract: BackgroundAfrican trypanosomiasis is a major disease of economic and public health importance affecting agricultural and human development. The search for alternative compounds against African trypanosomiasis is justified by various limitations of existing chemotherapeutic agents. This study was aimed at screening the hydromethanolic and dichloromethane (DCM) crude extracts of aerial parts of Artemisia abyssinica for in vivo antitrypanosomal activity against Trypanosoma congolense isolate in mice.MethodsThe ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
8
10
0
Order By: Relevance
“…Higher doses (250 and 200 mg/kg) of both extracts substantially reduced parasitemia level in mice, despite the failure to completely clear bloodstream form of the parasite. The result is consistent with other reports [ 25 , 28 ] that medicinal plants reduce parasitemia. The effect might be attributed to the presence in them of one or more of secondary metabolites which may exert their effects through the additive or synergistic action of several chemical compounds acting at a single or multiple target sites associated with a physiological process [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Higher doses (250 and 200 mg/kg) of both extracts substantially reduced parasitemia level in mice, despite the failure to completely clear bloodstream form of the parasite. The result is consistent with other reports [ 25 , 28 ] that medicinal plants reduce parasitemia. The effect might be attributed to the presence in them of one or more of secondary metabolites which may exert their effects through the additive or synergistic action of several chemical compounds acting at a single or multiple target sites associated with a physiological process [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…This may be credited to the presence of phenolic compounds in the DCM, but not in the MOH, extract as these compounds were shown to exhibit anti-trypanosomal activity [ 39 ]. Other report has shown similar observation that superior activity was obtained from the DCM plant extracts [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The cure rate of animals treated with 250 mg/kg of the extract was 100% and the animals remained aparasitemic for more than 60 days post infection. This is remarkable because previous studies (Ekanem et al 2008;Abu & Uchendu 2011;Tsegabirhan et al 2014;Feyera et al 2014) reported relapse when mice infected with trypanosomes are treated with either plant extracts or the commercial trypanocide (diminazine aceturate). For instance, Feyera et al (2014) reported that 400 mg/kg dichloromethane and 80% methanol extracts of Artemisia abyssinica Sch.…”
Section: Discussionmentioning
confidence: 87%